2020
DOI: 10.3389/fphar.2020.00394
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Talk Between the Dopaminergic and the Immune System Involved in Schizophrenia

Abstract: Dopamine is one of the neurotransmitters whose transmission is altered in a number of neural pathways in the brain of schizophrenic patients. Current evidence indicates that these alterations involve hyperactive dopaminergic transmission in mesolimbic areas, striatum, and hippocampus, whereas hypoactive dopaminergic transmission has been reported in the prefrontal cortex of schizophrenic patients. Consequently, schizophrenia is associated with several cognitive and behavioral alterations. Of note, the immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 184 publications
(299 reference statements)
1
47
0
1
Order By: Relevance
“…Because the data suggested that microglial cells might be intimately involved in the pathogenesis of schizophrenia [ 60 , 61 ], we explored potential alterations in the pro- ( MhcII , Cd40 , iNos , Il-1β , Tnf-α and Il-6 ) and anti-inflammatory ( Arg1 , Igf-1 , Tgf-β and Il-4 ) factors that are also considered microglial markers ( Figure 9 and Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because the data suggested that microglial cells might be intimately involved in the pathogenesis of schizophrenia [ 60 , 61 ], we explored potential alterations in the pro- ( MhcII , Cd40 , iNos , Il-1β , Tnf-α and Il-6 ) and anti-inflammatory ( Arg1 , Igf-1 , Tgf-β and Il-4 ) factors that are also considered microglial markers ( Figure 9 and Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, investigations on PFC during postnatal development revealed that DA homeostasis is tightly regulated by astroglial cells at this stage [ 13 ], thus highlighting the importance that glial cells play in regulating DA signaling during development. Indeed, several studies have confirmed that DA can exert either anti-inflammatory or pro-inflammatory effects in human and in vivo models through dopamine receptor activation on astrocytes and microglia [ 61 , 62 , 63 ]. In this framework, we sought to investigate the effects of DAT ablation in the prelimbic PFC, responsible for cognitive processing [ 64 ], that could lead to glial pro-inflammatory process that might contribute to the underlying pathophysiology of female DAT+/− and DAT−/− rats during early adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…A further aspect that we have not explored in this work is the dopaminergic regulation of the immune system. Immune cells, including T and B lymphocytes, dendritic cells, natural killer cells, macrophages, and microglia, express dopamine receptors and thus increased dopamine, as proposed to occur in schizophrenia, may itself regulate inflammatory activity [reviewed in ( 71 )]. Indeed, studies have identified B and T cells in the cortex and hippocampus of some people with schizophrenia ( 72 , 73 ), and investigating the presence of other peripheral immune cells in the midbrain and how these cells may be influenced by changes to dopamine or with antipsychotics in schizophrenia, is of interest.…”
Section: Discussionmentioning
confidence: 99%